2015
DOI: 10.1088/1741-2560/12/4/046022
|View full text |Cite
|
Sign up to set email alerts
|

Isolating gait-related movement artifacts in electroencephalography during human walking

Abstract: Objective High-density electroencephelography (EEG) can provide insight into human brain function during real-world activities with walking. Some recent studies have used EEG to characterize brain activity during walking, but the relative contributions of movement artifact and electrocortical activity have been difficult to quantify. We aimed to characterize movement artifact recorded by EEG electrodes at a range of walking speeds and to test the efficacy of artifact removal methods. We also quantified the sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
221
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(236 citation statements)
references
References 35 publications
14
221
1
Order By: Relevance
“…Furthermore, the signal correlation varied for each of the three EEG electrode locations (Cz, Oz, T8), suggesting that a uniform filtering method could not be used across all scalp electrodes (Castermans et al, 2014). Kline et al (2015) and Snyder et al (2015) used a silicone swim cap to block all electrocortical activity, thus measuring only movement artifact while subjects walked on a treadmill at different speeds. Like Castermans et al (2014) and Kline et al (2015) collected accelerometer data, however, there was poor correlation between the EEG and accelerometer signals.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the signal correlation varied for each of the three EEG electrode locations (Cz, Oz, T8), suggesting that a uniform filtering method could not be used across all scalp electrodes (Castermans et al, 2014). Kline et al (2015) and Snyder et al (2015) used a silicone swim cap to block all electrocortical activity, thus measuring only movement artifact while subjects walked on a treadmill at different speeds. Like Castermans et al (2014) and Kline et al (2015) collected accelerometer data, however, there was poor correlation between the EEG and accelerometer signals.…”
Section: Resultsmentioning
confidence: 99%
“…Note that physiological artifacts caused by electrical activity of the muscles are unavoidable, but may be relatively easy to deal with by temporal filter application and other post-processing procedures (Reis et al, 2014). Motion of sensors, and motion of parts of the measurement system, however, may contribute strong interference and corrupt signals to an extend that the underlying brain activity cannot be recovered (Kline et al, 2015). New hardware solutions that account for sensor motion (Yazicioglu et al, 2010; Reis et al, 2014; Cömert and Hyttinen, 2015; Goverdovsky et al, 2015) and miniaturized amplifier solutions featuring shielding and active amplification (Metting van Rijn et al, 1990) may help to alleviate this problem further.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies (Castermans et al, 2014;Kline et al, 2015) investigated movementrelated artifacts in the EEG during upright walking and found contamination of the EEG data at frequencies from 1 to 150 Hz. Castermans et al (2014) found similar time/frequency properties in accelerometer signals recorded from the head during walking and in EEG for frequency bands extending up to 150 Hz.…”
Section: Methodsmentioning
confidence: 99%